John Cloer at work in foam house facility at Hercules Brunswick plant - Hercules Incorporated (1960)
General view of safety inspector John Cloer at work in the foam house at the Hercules Powder Company plant in Brunswick, Georgia, with view of assorted fire-fighting and fire-suppression apparatus. One of two Hercules plants specializing in naval stores, the Brunswick plant extracted rosin, turpentine, and pine oil from pine tree stumps in order to produce a range of chemicals used in the manufacture of varnishes, paints, adhesives, insecticides, textiles, and other industrial products. Per notations accompanying the photograph, the plant boasted an elaborate and highly-developed automatic fire-fighting system as protection against the highly inflammable materials manufactured at the facility. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Naval stores industry; Employees; Chemical industry; Hercules Incorporated; Corporations; Naval stores; Fire extinction--Equipment and supplies; Machinery; Cloer, John